Magnetic Dipole Levitation - Simulation and Control Optimisation - Schimanski, Samuel (Wellington Faculty of Engineering Symposium, 2023)
Nuclear fusion has long been seen as the holy grail of clean energy. Fuelled by hydrogen isotopes deuterium and tritium, fusion offers the potential for near-limitless energy production due to hydrogen isotopes natural abundance. Many different approaches have been and are being taken to achieve fusion, arguably the world-leading approach being magnetic confinement. The most notable reactors are Tokamaks and Stellarators although, other forms of magnetic confinement reactors exist such as the levitated dipole reactor. First theorized by Akira Hasegawa and later brought to life by a team at MIT in the early 2000s under the name “Levitated Dipole Experiment” (LDX). As the name implies the device involves a magnetic dipole which is levitated by an external force to be used for plasma confinement. Specifically, an overhead magnet is used in levitation. This formation is inherently vertically unstable, requiring a feedback loop and control system to maintain stability. This paper discusses the development of a model of dipole-dipole interactions and the design and evaluation of several controllers. As this is a power system at heart, efficiency is a fundamental aspect to be considered. Therefore, any unnecessary power consumption during levitation will harm the reactor’s bottom line in terms of net power production. Thus, with efficiency in mind, these controllers were evaluated to determine any inherent advantages or disadvantages. Furthermore, the accuracy of the produced models was assessed to determine their reliability in being applied to arbitrary coil geometries.